Introduction: The Historiographical Legacies of David Underdown. Issue 5 (30th May 2013) - Smuts, Malcolm; Smuts, Malcolm
Abstract During a career spanning nearly six decades, David Underdown anticipated the turn toward detailed narrative political history characteristic of revisionism but subsequently rejected what he saw as an overly narrow revisionist emphasis on high politics, in favor of approaches that focused on the political outlooks of the majority of the population and connections between political, social and cultural history. This introduction reflects on the overall arc of his career, its relationship to the historiography of the late twentieth‐century and its relevance to the current state of the field of early seventeenth century English history.